THE EFFECT OF PROBLEM BASED LEARNING AND EXPOSITORY TOWARD LEARNING OUTCOMES OF CHRISTIAN EDUCATION COURSE - Handayani, Rini (Studies in Comparative Education, 2018)
Learning strategy of problem based learning becomes one of the alternative strategies to improve the learning outcomes in understanding concept application for students who took Christian Education course. This strategy could encourage students to understand the concept of learning through contextual problem solving. The objective of this study examined the effect of learning strategies – Problem based learning and Expository, toward learning outcomes of understanding concept application among students who took Christian education course. The design of this study used quasi experimental with non-equivalent control group design pattern. The subjects were 107 students of the Faculty of Agriculture and Faculty of Humanities in Brawijaya University. The participants were divided into two groups, the experimental group (problem based learning) with 62 students and the control group (expository) with 45 students. The results of the study can be summarized as follows: (1) there was an influence of learning strategies on learning outcomes in understanding concept application among students who took Christian Education course in Brawijaya University, (2) Problem Based Learning strategies affected more in learning outcomes of understanding Christian Education concept compared to expository learning strategies, (3) Problem Based Learning strategies were learning strategies that bring significant influence on learning outcomes in relation with understanding of Christian Education concept.